Rigid gas permeable contact lenses for visual rehabilitation of unilateral aphakic children in China. Issue 5 (October 2019) - Zhang, Xiaoxiao; Zeng, Junwen; Cui, Dongmei; Li, Zhouyue; Hu, Yin; Long, Wen; Yang, Xiao
Abstract: Purpose: To investigate the effectiveness, safety and tolerance of rigid gas-permeable contact lenses (RGP CLs) in the visual rehabilitation of unilateral aphakic children in China. Methods: Records of 36 children (36 eyes) with RGP CLs to unilateral aphakia between 2014 and 2018 were evaluated. Each enrolled child underwent vision assessment (visual acuity, fixation, and deviation) at each follow-up visit and their caregivers completed a questionnaire designed to find out the reasons for RGP CLs dropout. The fit characteristics and adverse events were also evaluated. Results: The mean age was 7.0 months (interquartile range, 5.0–12.8 months). The final mean logMAR visual acuity (VA) of the treated eyes was 1.2 ± 0.7 for 12 patients who cooperated in visual assessments and 6 out of these subjects had a VA of better than 1.0 logMAR. The proportion of treated eyes which could be recorded the visual results increased significantly after RGP CLs intervention (5.6% vs. 33.3%, P < 0.001). The final VA assessed for the fellow eyes and both eyes were 0.7 ± 0.4 and 0.6 ± 0.3, respectively. Of the 36 patients, 24 had strabismus. There was no severe lens-related adverse event except only one patient had mild conjunctivitis. At the end of the follow-up it was found that 25 eyes are still using RGP CLs (69%). Indications to discontinue contact lens wear included difficult manipulation of RGP CL, loss of motivation, unstable lens, and eye irritation. Conclusions: RGP contact lenses provide an effective and safe alternative method for visual rehabilitation and can be well tolerated in pediatric aphakia.